Dealing with high temperatures: A survey assessing the degree of heat risk awareness and the adaptation measures applied in hospitals and retirement homes in Berlin - Daniel Engler (2019)
Objectives: In particular vulnerable individuals have to cope with a changing climate, already now and increasingly in the future. The aim of this study was to assess the degree of heat risk awareness and adaptation measures applied in hospitals and retirement homes in Berlin. Methods: In a multi method approach a survey was developed and were sent to the care managers of all eligible stationary healthcare providers (HCP) in Berlin (N=357). The survey included questions on the presence of a heat action plans and cooling management facilities in the buildings. Furthermore, the care managers were asked to judge the importance of measures against heat related health risks, and to report practical problems that may affect the implementation of heat reduction measures. In addition, experts in this field were asked to report strategies that increase the awareness and the adaptation measures in hospitals and retirement homes in Berlin. Results: Of the 357 questionnaires sent, 35 were returned (13%). Strong associations between the increase in patient care during high temperatures and the increase of requirement of health care staff during those days could be statistically determined (r = .567, p = .001, n = 34). Association between heat risk awareness and heat risk adaptation could not be observed (F [1.24]= 1.563; p = 0.223). Most HCP had not a heat action plan. Sunshades were used most often to protect patients/residents against high temperatures (99% of all HCP). Prevalence of cooling facilities such as air conditioning and rooftop greenings are very low (2-5%). Care managers confirmed the importance of heat risk adaptation measures, with some exceptions. Barriers of heat action implementation mentioned related to building structure, storage among health care personnel and a lack of policy support of heat reduction measures. Conclusion: In general the implementation of heat adaptation strategies are rather on a sufficient minimum level. However, HCP are aware of heat related health impacts of their patients or residents and staff. Further development and implementation of heat adaptation is essential to protect the institutionalized patients and residents against future increase of high temperatures. Potential areas of improvement include the cooling of buildings and training of staff.